Peran Marketplace Terhadap UMKM Sebagai Upaya Percepatan Ekonomi Indonesia Di Masa Pandemi Covid-19 Dalam Perspektif Islam - Ajeng Sonial Manara (Universitas Hamzanwadi, 2022)
The relationship between UMKM and the Marketplace includes aspects of distribution and cooperation in achieving prosperity. Distribution is an important position of Islamic micro and macro theory because the discussion in the field of distribution is not only related to mere economic aspects but also social and political aspects so that it has become a concern for Islamic and conventional economic thinkers to date. This study will discuss the role of the Marketplace for UMKM as an effort to accelerate the Indonesian economy during the Covid-19 pandemic from an Islamic perspective. This study uses a qualitative phenomenological method. In the perspective of Islamic economics, the proportion of equity that is truly equal, the basis is that one's work ethic and abilities must be respected, the form of appreciation is an Islamic attitude that allows one person's income to be different from others, because of the efforts and endeavors described in the Qur'an. Surah an-Nahl verse 71. The role of the Marketplace towards UMKM in facilitating the distribution of goods and services in accordance with the great Islamic commitment to brotherhood and justice.